Emulsified compositions and cosmetics
By using an emulsion composition consisting of titanium-containing silicone resin, liquid oil, and water, the stickiness problem caused by surfactants is solved, resulting in improved stability and user experience, and giving cosmetics the ability to absorb ultraviolet rays.
Patent Information
- Application Number
- CN202180092916.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-02-10
- Filing Date
- 2021-12-07
- Publication Date
- 2025-12-09
- Estimated Expiration
- 2041-12-07
AI Technical Summary
The use of surfactants in existing emulsion compositions can cause a slippery or sticky feeling, which affects the user experience of cosmetics and makes it difficult to achieve improvements in stability and functionality.
An emulsion composition is formed by a silicone resin containing titanium atoms, a liquid oil soluble in hydrocarbon oil, ester oil or silicone oil, and water, avoiding the use of surfactants, and a stable emulsion composition is formed by silicone resin with specific structural units.
It achieves a non-sticky user experience and the coating with UV absorption effect improves the stability and usability of cosmetics.
Smart Images

Figure CN116806143B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to an emulsified composition and a cosmetic containing the same. BACKGROUND
[0002] In the past, silicone resins have been used as a cosmetic raw material for foundation, lipstick, eye shadow, mascara, and the like, cosmetics for preventing ultraviolet rays, cosmetics for hair, and the like, because of their film-forming ability, excellent water resistance, sweat resistance, and sebum resistance. For example, a skin cosmetic containing an organosilicon resin composed of units of the average formula R n SiO 4-n / 2 a skin cosmetic containing a resin composed of units of R3SiO 1 / 2 and SiO 4 / 2 units and a volatile silicone oil (Patent Document 2), a sunscreen cosmetic blended with a silicone resin containing two or more units of R2SiO 2 / 2 units, RSiO 3 / 2 units, SiO 4 / 2 units, and optionally capped with R3SiO 1 / 2 units, a volatile oil agent, and an ultraviolet absorber and / or an ultraviolet scatterer (Patent Document 3), and the like, disclose that these cosmetics can provide a film with excellent water resistance.
[0003] Further, silicone resins can be used with a surfactant to form an emulsified composition with water. It is known that by making a silicone resin into an emulsified composition, a moist and smooth touch can be imparted when used as a cosmetic. Generally, in order to ensure stability over time, an emulsified composition must use a surfactant, but there is a problem of a slippery or sticky feeling from the surfactant, and improvement in the feeling of use is sought.
[0004] In recent years, in order to impart further functionality to silicone resins, an organosilicon resin containing different kinds of metals with excellent water repellency and oil repellency has been developed (Patent Document 4). It is disclosed that a silicone resin having a titanium atom has ultraviolet absorption ability, and a cosmetic containing the silicone resin has excellent adhesion to the skin, excellent cosmetic effect persistence, and excellent anti-transfer effect. In addition, it is also suggested that an emulsified cosmetic is made using a conventional emulsification technique, but the use of a surfactant is taken as a premise, and similarly, the problem of the feeling of use from the surfactant remains.
[0005] PRIOR ART DOCUMENTS
[0006] PATENT DOCUMENTS
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 61-158910
[0008] Patent Literature 2: Japanese Patent Application Laid-Open (JP-A) No. 61-65808
[0009] Patent Literature 3: Japanese Patent Application Laid-Open (JP-A) No. 62-234012
[0010] Patent Literature 4: Japanese Patent Application Laid-Open (JP-A) No. 11-193209 SUMMARY
[0011] PROBLEMS TO BE SOLVED BY THE INVENTION
[0012] The present application has been achieved in view of the above-described circumstances, and aims to provide an emulsified composition which is excellent in stability and use properties and does not use a surfactant, and a cosmetic containing the above-described emulsified composition.
[0013] MEANS OF SOLVING THE PROBLEMS
[0014] To solve the above-described problems, the present application provides an emulsified composition which contains
[0015] (A) : a silicon resin containing a titanium atom,
[0016] (B) : an oil agent which is soluble in the component (A) and is liquid at 25°C, selected from one or more of the group consisting of a hydrocarbon oil, an ester oil and a silicone oil,
[0017] (C) : water,
[0018] and does not contain a surfactant.
[0019] If it is such an emulsified composition, it is an emulsified composition which is excellent in stability and use properties and does not use a surfactant.
[0020] Further, the component (A) is preferably a silicon resin containing a titanium atom represented by the following compositional formula (1),
[0021] [Chemical Formula 1]
[0022] [R3SiO 1 / 2 ] a [RSiO 3 / 2 ] b [SiO 4 / 2 ] c [TiO 4 / 2 ] d (1)
[0023] in the formula, R is independently a group selected from an alkyl group having 1 to 8 carbon atoms, an aryl group having 6 to 12 carbon atoms and a fluorine-substituted alkyl group having 1 to 8 carbon atoms, a is 0.01 to 0.7, b is 0 to 0.9, c is 0.01 to 0.7, d is 0.01 to 0.3, and a + b + c + d is 1.0.
[0024] If the above-mentioned (A) component is such a component, an emulsified composition which does not use a surfactant and is excellent in stability and usability can be more easily obtained.
[0025] Further, it is preferable to contain 0.1 to 30.0 mass% of the above-mentioned (A) component.
[0026] If the ratio of the above-mentioned (A) component is such a ratio, emulsification can be more easily performed.
[0027] Further, a cosmetic containing the above-mentioned emulsified composition is provided.
[0028] If it is such a cosmetic, since it does not contain a surfactant, when used as an emulsified cosmetic, a cosmetic which does not have a slimy or sticky feeling from the surfactant and is excellent in usability can be obtained.
[0029] Effects of the Invention
[0030] According to the present application, by using a silicon resin containing a titanium atom having a specific structural unit, an emulsified composition which does not use a surfactant and is excellent in stability and usability can be obtained. Further, after application, a coating film having an ultraviolet absorbing effect can be formed. Further, by using the emulsified composition of the present application, a cosmetic which is excellent in usability can be provided. BRIEF DESCRIPTION OF DRAWINGS
[0031] Figure 1 One example of an IR spectrum of a silicon resin synthesized in Examples and Comparative Examples.
[0032] Figure 2 One example of a UV spectrum of a silicon resin synthesized in Examples and Comparative Examples. DETAILED DESCRIPTION
[0033] As described above, an emulsified composition which does not use a surfactant and is excellent in stability and usability is sought to be obtained.
[0034] In order to solve the above-mentioned technical problem, the inventors of the present application have conducted earnest research repeatedly, and as a result, have found that by using a silicon resin containing a titanium atom having a specific structural unit, an emulsified composition which does not use a surfactant and is excellent in stability and usability can be obtained, thereby completing the present application.
[0035] That is, the present application is an emulsified composition containing
[0036] (A) a silicon resin containing a titanium atom,
[0037] (B) an oil agent which is soluble in the above-mentioned (A) component and is liquid at 25°C, selected from one or more of the group consisting of a hydrocarbon oil, an ester oil and a silicone oil,
[0038] (C) : water,
[0039] and does not contain a surfactant.
[0040] Hereinafter, the present application will be described in detail, but the present application is not limited thereto.
[0041] [(A) Silicon Resin Containing Titanium Atom]
[0042] The (A) component of the present application is a silicon resin containing a titanium atom, specifically, for example, a silicon resin having a titanoxane unit (TiO 4 / 2 unit) in the molecule. Among them, a silicon resin containing a titanium atom represented by the following formula (1) is preferable.
[0043] [Chemical Formula 2]
[0044] [R3SiO 1 / 2 ] a [RSiO 3 / 2 ] b [SiO 4 / 2 ] c [TiO 4 / 2 ] d (1)
[0045] The above R is independently a group selected from an alkyl group having 1 to 8 carbon atoms, an aryl group having 6 to 12 carbon atoms, and a fluorine-substituted alkyl group having 1 to 8 carbon atoms.
[0046] As the alkyl group having 1 to 8 carbon atoms, a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, and an octyl group can be exemplified. As the aryl group having 6 to 12 carbon atoms, a phenyl group, a tolyl group, and the like can be exemplified. As the fluorine-substituted alkyl group having 1 to 8 carbon atoms, a trifluoropropyl group, and the like can be exemplified.
[0047] Among them, an alkyl group having 1 to 3 carbon atoms is more preferable, and a methyl group is further preferable.
[0048] The above a is a number of 0.01 to 0.7, preferably 0.1 to 0.7, and more preferably 0.2 to 0.6. If a is 0.01 or more, gelation does not occur at the time of production, and if it is 0.7 or less, the resin coating film does not become sticky or liquid.
[0049] The above b is a number of 0 to 0.9, preferably 0 to 0.8, and more preferably b = 0. If b is 0.9 or less, gelation does not occur.
[0050] The above c is a number of 0.01 to 0.7, preferably 0.2 to 0.7, and more preferably 0.3 to 0.6. If it is 0.01 or more, the resin coating film does not become sticky or liquid, and if it is 0.7 or less, gelation does not occur.
[0051] The above d is preferably 0.01 to 0.3, more preferably 0.04 to 0.2, and further preferably 0.05 to 0.15. If it is 0.01 or more, emulsion stability can be ensured, and if it is 0.3 or less, gelation does not occur. Furthermore, from the viewpoint of obtaining higher emulsion stability, it is preferable that the value of d be large.
[0052] Furthermore, with respect to the above a, the above b, the above c, and the above d, a + b + c + d is 1.0.
[0053] In the above composition formula (1), the silicon resin containing a titanium atom represented by the following composition formula (2) in which R is a methyl group is particularly preferable.
[0054] [Chemical Formula 3]
[0055] [(CH3)3SiO 1 / 2 ] a [CH3SiO 3 / 2 ] b [SiO 4 / 2 ] c [TiO 4 / 2 ] d (2)
[0056] In the formula, a, b, c, and d are the same as the above a, b, c, and d.
[0057] The weight average molecular weight of the silicon resin containing a titanium atom in the present application is preferably 500 to 20,000, and more preferably 1,000 to 8,000. If it is within this range, compatibility with an oil agent is good, and a hard coating film that is not sticky can be obtained, and thus it is preferable. In the present application, the weight average molecular weight is a value obtained by GPC (gel permeation chromatography) analysis using polystyrene as a standard substance based on the following conditions.
[0058] [Measurement Conditions]
[0059] Eluent: Tetrahydrofuran (THF)
[0060] Flow rate: 0.6 mL / min
[0061] Detector: Differential refractive index detector (RI)
[0062] Column: TSK Guard column Super H-H
[0063] TSK gel Super H-M-N (6.0 mm I.D. x 15 cm x 1)
[0064] TSK gel Super H2500 (6.0 mm I.D. x 15 cm x 1)
[0065] (All manufactured by TOSOH CORPORATION)
[0066] Column temperature: 40°C
[0067] Sample injection amount: 50 μL (0.3 mass% THF solution)
[0068] [(B) Oil agent]
[0069] The oil agent of the (B) component is an oil agent that is soluble in the above-mentioned (A) component and is liquid at 25°C, and is one or more selected from the group consisting of a hydrocarbon oil, an ester oil, and a silicone oil.
[0070] As the hydrocarbon oil, liquid paraffin, hydrogenated polyisobutene, hydrogenated polydecene, squalane, squalene, pristane, light isoparaffin, light liquid isoparaffin, heavy liquid isoparaffin, liquid isoparaffin, tetradecene, isohexadecane, isododecane, a-olefin oligomer, and the like can be exemplified. Isododecane can be preferably exemplified.
[0071] As the ester oil, ethyl oleate, ethyl linoleate, isopropyl myristate, isopropyl palmitate, isopropyl isostearate, cetyl ethylhexanoate, isocetyl ethylhexanoate, stearyl ethylhexanoate, isostearyl ethylhexanoate, cetyl palmitate, 2-ethylhexyl palmitate, cetyl decanoate, isostearyl isostearate, trimethylolpropane triisostearate, myristyl myristate, cetyl palmitate, isocetyl isostearate, isostearyl isostearate, isodecyl isononanoate, 2-ethylhexyl isononanoate, isodecyl isononanoate, isotridecyl isononanoate, octyldodecyl erucate, neopentyl glycol dicaprate, pentaerythrityl tetraethylhexanoate, diisostearyl malate, trimethylolpropane tri(ethylhexanoate), sebacyl diisocaprylate, cholesteryl isostearate, batyl isostearate, hydrogenated castor oil monohydroxystearate, isostearyl lanolate, isopropyl lanolate, octyldodecyl lanolate, cetyl ricinoleate, dioctyl succinate, cetyl lactate, propylene glycol dicaprylate, propylene glycol dicaprate, propylene glycol dinonanate, propylene glycol dicaprylate / dicaprate, propylene glycol diisostearate, propylene glycol dioleate, a triglyceride, a plant and animal oil, and the like can be exemplified. As the triglyceride, a triglyceride of glycerin and hexanoic acid, octanoic acid, decanoic acid, 2-ethylhexanoic acid, isotridecanoic acid, isopalmitic acid, isostearic acid, eicosanoic acid, oleic acid, and the like can be exemplified. As the plant and animal oil, olive oil, sunflower oil, safflower oil, castor oil, camellia oil, and the like can be exemplified.
[0072] As the silicone oil, low- to high- viscosity linear or branched organic polysiloxanes such as dimethylpolysiloxane, methyltris(trimethylsiloxy)silane, octanoylpolymethylsiloxane, phenylpolymethylsiloxane, methylhexylpolysiloxane, methylhydrogenpolysiloxane, dimethylsiloxane-methylphenylsiloxane copolymer, cyclic organic polysiloxanes such as octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, dodecamethylcyclohexasiloxane, tetramethyltetrahydrocyclotetrasiloxane, tetramethyltetraphenylcyclotetrasiloxane, amino-modified organic polysiloxane, pyrrolidone-modified organic polysiloxane, pyrrolidone carboxylic acid-modified organic polysiloxane, higher alkoxy-modified organic silicone such as stearyloxyorganosilicon, higher fatty acid-modified organic silicone, alkyl-modified organic silicone, long-chain alkyl-modified organic silicone, amino acid-modified organic silicone, fluorine-modified organic silicone, and the like can be exemplified.
[0073] [(C) water]
[0074] The water of the component (C) is not particularly limited, and purified water and the like can be exemplified.
[0075] [Emulsified composition]
[0076] The emulsified composition of the present application contains the components (A) to (C).
[0077] In the emulsified composition of the present application, the components (A) and (B) form an oil layer, and the component (C) forms a water layer. The form of the emulsified composition of the present application is not particularly limited, and can be, for example, an O / W emulsion in which oil droplets are dispersed in water, or a W / O emulsion in which water droplets are dispersed in oil. In addition, the ratio of the component (A) to the component (B) in the oil layer can be uniform, or the component (A) can be biased toward the surface side of the oil layer.
[0078] The ratio of the component (A) to the component (B) in the oil layer is not particularly limited, and the value of the component (A) : the component (B) is preferably 0.1 : 19.9 to 10 : 10, more preferably 0.2 : 19.8 to 7.5 : 12.5, further preferably 0.5 : 19.5 to 5 : 15, and most preferably 1 : 19 to 3 : 17.
[0079] In the emulsified composition of the present application, the mass ratio of the admixture of the components (A) to (C) is preferably the following value.
[0080] (A): 0.1 to 30 mass%, preferably 0.1 to 20 mass%, and further preferably 0.1 to 10 mass%.
[0081] (B): 1.0 to 40 mass%, preferably 1.0 to 20 mass%, and further preferably 1.0 to 10 mass%.
[0082] (C): 50.0 to 99.0 mass%, preferably 70.0 to 99.0, further preferably 80 to 99.0 mass%.
[0083] The emulsified composition of the present application is characterized by not containing a surfactant. Thus, the emulsified composition can be produced without using a surfactant, and the effect of the titanium atom-containing silicone resin of component (A) is exhibited.
[0084] < Cosmetics >
[0085] The emulsified composition of the present application can be applied, for example, to moisturizing creams, emulsified foundations, sunscreen lotions, hair creams, cream preparations, and the like. Since it does not contain a surfactant, when used as such emulsified cosmetics, there is no slimy or sticky feeling from the surfactant, and a cosmetic with excellent use feeling can be obtained, and thus it is preferred.
[0086] Examples
[0087] Hereinafter, examples and comparative examples are shown, and the present application is specifically described, but the present application is not limited by the following examples. In the following examples, " % " means mass% unless specifically noted otherwise. Furthermore, (CH3)3SiO 1 / 2 units are denoted as M units, CH3SiO 3 / 2 units are denoted as T units, SiO 4 / 2 units are denoted as Q units, TiO 4 / 2 units are denoted as Ti units.
[0088] [Example 1]
[0089] In a reactor, 26.18 g of hexamethyldisiloxane, 74.68 g of tetraethoxysilane, and 64 g of isopropyl alcohol (hereinafter, referred to as IPA) were added, and 0.64 g of methanesulfonic acid was added, and cooled to 10 to 20°C, and 47.54 g of water was added dropwise while stirring. After the dropwise addition was completed, hydrolysis and condensation reactions were performed at 50 to 80°C for 5 hours, and a silicone resin solution was obtained.
[0090] Next, 1.03 g of 25% sodium hydroxide aqueous solution and 0.13 g of calcium carbonate were added, and after the acid was neutralized, 100 g of isododecane was added, heated to 90 to 115°C, and after the generated ethanol, IPA, excess water were removed and cooled, 3.96 g of tetraisopropyl titanate was added dropwise while stirring, and after stirring for 2 hours, heating was performed at 130°C for 3 hours, and after the generated IPA and water were removed, cooling was performed. Further, after removal by reduced pressure distillation, the silicon resin concentration was diluted to 60% using isododecane as an oil agent, and then filtration was performed, whereby a 60% silicon resin isododecane solution was obtained in which the molar ratio of M unit:Q unit:Ti unit was 0.46:0.52:0.02.
[0091] [Example 2]
[0092] In a reactor, 26.18 g of hexamethyldisiloxane, 74.68 g of tetraethoxysilane, and 64 g of IPA were added, and 0.64 g of methanesulfonic acid was added, and cooled to 10 to 20°C, and 47.54 g of water was added dropwise while stirring. After the end of the dropwise addition, hydrolysis and condensation reactions were performed by heating at 50 to 80°C for 5 hours, and a silicon resin solution was obtained.
[0093] Next, 1.03 g of 25% sodium hydroxide aqueous solution and 0.13 g of calcium carbonate were added, and after the acid was neutralized, 100 g of isododecane was added, heated to 90 to 115°C, and after the generated ethanol, IPA, excess water were removed and cooled, 3.96 g of tetraisopropyl titanate was added dropwise while stirring, and after stirring for 2 hours, heating was performed at 130°C for 3 hours, and after the generated IPA and water were removed, cooling was performed. Further, after removal by reduced pressure distillation, the silicon resin concentration was diluted to 60% using isododecane as an oil agent, and then filtration was performed, whereby a 60% silicon resin isododecane solution was obtained in which the molar ratio of M unit:Q unit:Ti unit was 0.46:0.52:0.02.
[0094] [Example 3]
[0095] In a reactor, 26.18 g of hexamethyldisiloxane, 74.68 g of tetraethoxysilane, and 64 g of IPA were added, and 0.64 g of methanesulfonic acid was added, and cooled to 10 to 20°C, and 47.54 g of water was added dropwise while stirring. After the end of the dropwise addition, hydrolysis and condensation reactions were performed by heating at 50 to 80°C for 5 hours, and a silicon resin solution was obtained.
[0096] Next, 1.03 g of 25% sodium hydroxide aqueous solution and 0.13 g of calcium carbonate were added, and after the acid was neutralized, 100 g of isododecane was added, heated to 90 to 115°C, and after the generated ethanol, IPA, excess water were removed and cooled, 8.08 g of tetraisopropyl titanate was added dropwise while stirring, and after stirring for 2 hours, heating was performed at 130°C for 3 hours, and after the generated IPA and water were removed, cooling was performed. Further, after removal by reduced pressure distillation, the silicon resin concentration was diluted to 60% using isododecane as an oil agent, and then filtration was performed, whereby a 60% silicon resin isododecane solution was obtained in which the molar ratio of M unit:Q unit:Ti unit was 0.46:0.50:0.04.
[0097] [Example 4]
[0098] In a reactor, 26.18 g of hexamethyldisiloxane, 74.68 g of tetraethoxysilane, and 64 g of IPA were added, and 0.64 g of methanesulfonic acid was added, and cooled to 10 to 20°C, and 47.54 g of water was added dropwise while stirring. After the end of the dropwise addition, hydrolysis and condensation reactions were performed by heating at 50 to 80°C for 5 hours, and a silicon resin solution was obtained.
[0099] Next, 1.03 g of 25% sodium hydroxide aqueous solution and 0.13 g of calcium carbonate were added, and after the acid was neutralized, 100 g of isododecane was added, heated to 90 to 115°C, and after the generated ethanol, IPA, excess water were removed and cooled, 8.08 g of tetraisopropyl titanate was added dropwise while stirring, and after stirring for 2 hours, heating was performed at 130°C for 3 hours, and after the generated IPA and water were removed, cooling was performed. Further, after removal by reduced pressure distillation, the silicon resin concentration was diluted to 60% using isododecane as an oil agent, and then filtration was performed, whereby a 60% silicon resin isododecane solution was obtained in which the molar ratio of M unit:Q unit:Ti unit was 0.46:0.50:0.04.
[0100] [Example 5]
[0101] In a reactor, 26.18 g of hexamethyldisiloxane, 74.68 g of tetraethoxysilane, and 64 g of IPA were added, and 0.64 g of methanesulfonic acid was added, and cooled to 10 to 20°C, and 47.54 g of water was added dropwise while stirring. After the end of the dropwise addition, hydrolysis and condensation reactions were performed by heating at 50 to 80°C for 5 hours, and a silicon resin solution was obtained.
[0102] Next, 1.03 g of 25% sodium hydroxide aqueous solution and 0.13 g of calcium carbonate were added, and after the acid was neutralized, 100 g of isododecane was added, heated to 90 to 115°C, and after the generated ethanol, IPA, excess water were removed and cooled, 12.37 g of tetraisopropyl titanate was added dropwise while stirring, and after stirring for 2 hours, heating was performed at 130°C for 3 hours, and after the generated IPA and water were removed, cooling was performed. Further, after removal by reduced pressure distillation, the silicon resin concentration was diluted to 60% using isododecane as an oil agent, and then filtration was performed, whereby a 60% silicon resin isododecane solution was obtained in which the molar ratio of M unit:Q unit:Ti unit was 0.45:0.49:0.06.
[0103] [Example 6]
[0104] In a reactor, 26.18 g of hexamethyldisiloxane, 74.68 g of tetraethoxysilane, and 64 g of IPA were added, and 0.64 g of methanesulfonic acid was added, and cooled to 10 to 20°C, and 47.54 g of water was added dropwise while stirring. After the end of the dropwise addition, hydrolysis and condensation reactions were performed by heating at 50 to 80°C for 5 hours, and a silicon resin solution was obtained.
[0105] Next, 1.03 g of 25% sodium hydroxide aqueous solution and 0.13 g of calcium carbonate were added, and after the acid was neutralized, 100 g of isododecane was added, heated to 90 to 115°C, and after the generated ethanol, IPA, excess water were removed and cooled, 12.37 g of tetraisopropyl titanate was added dropwise while stirring, and after stirring for 2 hours, heating was performed at 130°C for 3 hours, and after the generated IPA and water were removed, cooling was performed. Further, after removal by reduced pressure distillation, the silicon resin concentration was diluted to 60% using isododecane as an oil agent, and then filtration was performed, whereby a 60% silicon resin isododecane solution was obtained in which the molar ratio of M unit:Q unit:Ti unit was 0.45:0.49:0.06.
[0106] [Example 7]
[0107] In a reactor, 23.27 g of hexamethyldisiloxane, 74.68 g of tetraethoxysilane, and 64 g of IPA were added, and 0.64 g of methanesulfonic acid was added, and cooled to 10 to 20°C, and 47.54 g of water was added dropwise while stirring. After the end of the dropwise addition, hydrolysis and condensation reactions were performed by heating at 50 to 80°C for 5 hours, and a silicon resin solution was obtained.
[0108] Next, 1.03 g of 25% sodium hydroxide aqueous solution and 0.13 g of calcium carbonate were added, and after the acid was neutralized, 100 g of isododecane was added, heated to 90 to 115°C, and after the generated ethanol, IPA, excess water were removed and cooled, 15.97 g of tetraisopropyl titanate was added dropwise while stirring, and after stirring for 2 hours, heating at 130°C was performed for 3 hours, and after the generated IPA and water were removed, cooling was performed. Further, after removal by reduced pressure distillation, the silicon resin concentration was diluted to 60% using isododecane as an oil agent, and then filtration was performed, whereby a 60% silicon resin isododecane solution was obtained in which the molar ratio of M unit:Q unit:Ti unit was 0.41:0.51:0.08.
[0109] [Example 8]
[0110] In a reactor, 26.18 g of hexamethyldisiloxane, 12.78 g of triethoxymethylsilane, 59.75 g of tetraethoxysilane, and 64 g of IPA were added, and 0.64 g of methanesulfonic acid was added, cooled to 10 to 20°C, and 47.54 g of water was added dropwise while stirring. After the end of the dropwise addition, hydrolysis and condensation reactions were performed by heating at 50 to 80°C for 5 hours, and a silicon resin solution was obtained.
[0111] Next, 1.03 g of 25% sodium hydroxide aqueous solution and 0.13 g of calcium carbonate were added, and after the acid was neutralized, 100 g of isododecane was added, heated to 90 to 115°C, and after the generated ethanol, IPA, excess water were removed and cooled, 21.54 g of tetraisopropyl titanate was added dropwise while stirring, and after stirring for 2 hours, heating at 130°C was performed for 3 hours, and after the generated IPA and water were removed, cooling was performed. Further, after removal by reduced pressure distillation, the silicon resin concentration was diluted to 60% using isododecane as an oil agent, and then filtration was performed, whereby a 60% silicon resin isododecane solution was obtained in which the molar ratio of M unit:Q unit:Ti unit was 0.43:0.09:0.38:0.10.
[0112] [Comparative Example 1]
[0113] In a reactor, 26.18 g of hexamethyldisiloxane, 74.68 g of tetraethoxysilane, and 64 g of IPA were added, and 0.64 g of methanesulfonic acid was added, cooled to 10 to 20°C, and 47.54 g of water was added dropwise while stirring. After the end of the dropwise addition, hydrolysis and condensation reactions were performed by heating at 50 to 80°C for 5 hours, and a silicon resin solution was obtained.
[0114] Next, 1.03 g of a 25% sodium hydroxide aqueous solution and 0.13 g of calcium carbonate were added, and after the acid was neutralized, 100 g of isododecane was added, and heating was performed at 130°C for 3 hours, and the generated ethanol, IPA, and excess water were removed, and cooling was performed. Further, after removal by reduced pressure distillation, the silicon resin concentration was diluted to 60% using isododecane as an oil agent, and then filtration was performed, and thus a 60% silicon resin isododecane solution was obtained in which the molar ratio of the M unit:Q unit was 0.47:0.53.
[0115] [Comparative Example 2]
[0116] In a reactor, 26.18 g of hexamethyldisiloxane, 6.39 g of triethoxymethylsilane, 67.23 g of tetraethoxysilane, and 64 g of IPA were added, and 0.64 g of methanesulfonic acid was added, and cooling was performed to 10-20°C, and 47.54 g of water was added dropwise while stirring. After the dropwise addition was completed, hydrolysis and condensation reactions were performed by heating at 50-80°C for 5 hours, and a silicon resin solution was obtained.
[0117] Next, 1.03 g of a 25% sodium hydroxide aqueous solution and 0.13 g of calcium carbonate were added, and after the acid was neutralized, 100 g of isododecane was added, and heating was performed at 130°C for 3 hours, and the generated ethanol, IPA, and excess water were removed, and cooling was performed. Further, after removal by reduced pressure distillation, the silicon resin concentration was diluted to 60% using isododecane as an oil agent, and then filtration was performed, and thus a 60% silicon resin isododecane solution was obtained in which the molar ratio of the M unit:Q unit was 0.47:0.53.
[0118] The molar ratio of the structural units, the refractive index, the kinematic viscosity, and the like of each of the silicon resins obtained in the above examples are shown in Table 1 below. In addition, the refractive index and the viscosity below are values obtained by measuring a resin solution in the concentration described in each table.
[0119] [Table 1]
[0120]
[0121] * The molar ratio of the composition is a value calculated from the addition ratio of the raw materials.
[0122] * The refractive index is a value at 25°C (nD25) measured using an Abbe refractometer as described in JIS K 0062:1992 D )
[0123] * The kinematic viscosity is a value at 25°C measured using a Cannon-Fenske viscometer as described in JIS Z 8803:2011
[0124] D5: Decamethylcyclopentasiloxane
[0125] ID: isododecane
[0126] [Infrared absorption characteristics]
[0127] Using an infrared spectrophotometer Nicolet iS50 (manufactured by Thermo Fisher Scientific Inc.), the IR spectrum was measured for the silicon resin solution obtained in the examples and comparative example, which was applied to a KBr cuvette. The measurement results are shown in FIG. 1. A is the IR spectrum of Comparative Example 1, B is the IR spectrum of Example 4, and C is the IR spectrum of Example 7. Figure 1
[0128] In Examples 4 and 7 in which the silicon resin containing titanium atoms was blended, a peak from Ti-O-Si (945 cm -1 near) was confirmed, which was not confirmed in Comparative Example 1 in which the silicon resin not containing titanium atoms was blended.
[0129] [Ultraviolet absorption characteristics]
[0130] Using an ultraviolet spectrophotometer UV-2200 (manufactured by SHIMADZU CORPORATION), the UV spectrum of the solution obtained by diluting the silicon resin solution obtained in the examples and comparative example to 1 g / L with isopropyl alcohol was measured using a quartz glass cuvette with a thickness of 10 mm. The measurement results are shown in FIG. 2. A is the result of the UV spectrum of Comparative Example 1, B is the result of the UV spectrum of Example 2, C is the result of the UV spectrum of Example 4, D is the result of the UV spectrum of Example 6, and E is the result of the UV spectrum of Example 7. Figure 2
[0131] It was confirmed that the more the content of titanium atoms in the resin, the more the ultraviolet absorption ability increased. In addition, since the silicon resin containing titanium atoms has ultraviolet absorption ability, an emulsion obtained by applying the silicon resin containing titanium atoms as an emulsifier was able to obtain a coating film having an ultraviolet resistance effect.
[0132] [Emulsification characteristics]
[0133] Using the silicon resin solution obtained in the above examples, the emulsification characteristics were confirmed. The blending amount is shown in Table 2.
[0134] [Table 2]
[0135]
[0136] * Oil agent used in the solution when the oil agent is a synthetic resin
[0137] In a container, each of the silicone resins and the oil agent was taken, and using a homogenizing disperser (manufactured by PRIMIX Corporation), after stirring at 500 rpm for 1 minute, water was slowly added while stirring. After the water was added, stirring was performed at 1,000 rpm for 5 minutes to prepare an emulsion. The emulsion was left in a constant-temperature dryer at 25°C overnight, and the stability of the emulsion was confirmed by visual observation. The results are shown in Table 3.
[0138] [Table 3]
[0139]
[0140] (Note 1) Manufactured by Shin-Etsu Chemical Co., Ltd.: KF-6017
[0141] (Note 2) Manufactured by Shin-Etsu Chemical Co., Ltd.: KSG-320
[0142] In Comparative Examples 1 and 2 in which a silicone resin not containing titanium atoms was used, no emulsion was obtained, but in Examples 1 to 8 in which a silicone resin containing titanium atoms was used, an emulsion was obtained, and even if no emulsifier was used, an emulsified composition was obtained. Further, it was found that as the content of titanium atoms increased, the amount of resin required for emulsification decreased, and the emulsifying ability improved. Furthermore, the emulsifying performance was higher than that of a polyether-modified silicone, which is an emulsifier of the organosilicon type.
[0143] Using the silicone resin solution containing titanium atoms obtained in the above examples, an emulsified composition was prepared, and the use feeling (sticky feeling) was evaluated.
[0144] [Use Evaluation]
[0145] With respect to the emulsified compositions obtained according to the following formulation Table 5, 50 female professional evaluators evaluated the spreadability at the time of application (spreading property), sticky feeling, and refreshing feeling according to the evaluation criteria shown in Table 4 below, and the average score of the evaluation results was calculated.
[0146] [Table 4]
[0147] Score Spread Sticky Freshness 5 Good None Good 4 Fairly good Almost none Fairly good 3 Average Average Average 2 Fairly poor Slightly sticky Fairly poor 1 Poor Sticky Poor
[0148] Based on the following, the results are shown in Table 5 according to the average score of the evaluation results.
[0149] ◎: Average score of 4.0 or more
[0150] O: Average score of 3.0 or more and less than 4.0
[0151] Δ: Average score of 2.0 or more and less than 3.0
[0152] X: average score less than 2.0
[0153] [Table 5]
[0154]
[0155] As shown in Table 5, the cosmetic of the present application is excellent in all evaluation items compared with the comparative example.
[0156] Therefore, it is understood that by using the silicon resin containing titanium atom, an emulsified composition having a non-sticky use feeling can be obtained.
[0157] Further, the present application is not limited to the above-described embodiments. The above-described embodiments are illustrative, and technical solutions having substantially the same configuration as the technical concept described in the claims of the present application and exerting the same effects are included in the technical scope of the present application.
Claims
1. An emulsified composition, characterized by, The emulsified composition contains (A): a silicon resin containing a titanium atom, (B): an oil agent that is liquid at 25°C and soluble in the (A) component, selected from one or more of the group consisting of a hydrocarbon oil, an ester oil, and a silicone oil, (C): water, and does not contain a surfactant, and the (A) component is a silicon resin containing a titanium atom represented by the following compositional formula (1), [R3SiO 1 / 2 ] a [RSiO 3 / 2 ] b [SiO 4 / 2 ] c [TiO 4 / 2 ] d (1) in formula (1), R is independently a group selected from an alkyl group having 1 to 8 carbon atoms, an aryl group having 6 to 12 carbon atoms, and a fluorine-substituted alkyl group having 1 to 8 carbon atoms, a is 0.01 to 0.7, b is 0 to 0.9, c is 0.01 to 0.7, d is 0.01 to 0.3, and a + b + c + d is 1.0; The emulsified composition contains 0.1 to 30 mass% of the (A) component, 1.0 to 40 mass% of the (B) component, and 50.0 to 99.0 mass% of the (C) component.
2. A cosmetic which is a cosmetic containing the emulsified composition according to claim 1, characterized by, The cosmetic does not contain a surfactant.
Citation Information
Patent Citations
Skin cosmetic
JP1986065808A
Skin cosmetic
JP1986158910A
Anti-suntan cosmetic
JP1987234012A
Silicone composite particles, making method and cosmetic composition
CN102061092A
Organosilicon resin containing dissimilar metal and cosmetic
JP1999193209A